2019
DOI: 10.1021/acssuschemeng.8b05613
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Tagged Chiral Ligands for Asymmetric Transfer Hydrogenations in Aqueous Medium

Abstract: We report the design and synthesis of novel ion-tagged chiral ligands for asymmetric transfer hydrogenation (ATH) in aqueous medium. Based on (R,R)-1,2-diphenylethylene diamine (DPEN) as structural motif, a straightforward three-step protocol was developed that gave access to novel chiral ligands with carbamate-substructure and pyridinium headgroup. The careful optimization of steric and electronic properties in combination with the adaption of solubility via choice of the anion gave a set of chiral and water-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Further studies on the effect of temperature showed that a lower yield can be compensated with increasing temperature (entries 10–14). , The excellent enantioselectivity was maintained even at a temperature of 70 °C, which is in accordance with our previous observations . The results for entries 15–18 suggest that the addition of an appropriate amount of water (i.e., decreasing γ while keeping the ionic liquid amount constant at 0.3 g) is beneficial to increase the yield of the reaction.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Further studies on the effect of temperature showed that a lower yield can be compensated with increasing temperature (entries 10–14). , The excellent enantioselectivity was maintained even at a temperature of 70 °C, which is in accordance with our previous observations . The results for entries 15–18 suggest that the addition of an appropriate amount of water (i.e., decreasing γ while keeping the ionic liquid amount constant at 0.3 g) is beneficial to increase the yield of the reaction.…”
Section: Resultssupporting
confidence: 86%
“…To solve this issue, a number of water-soluble ligands and catalysts have been developed for asymmetric transfer hydrogenations of ketones in aqueous media, providing the desired secondary alcohols in high yield and enantioselectivity. ,, Several strategies have been pursued to improve not only the water-solubility of the TsDPEN structural motive, including the modification with anionic groups in case of aryl sulfonated systems (e.g. : ( R,R )- 1 , ( R,R )- 2 ) and the functionalization with cationic groups such as trialkylammonium moieties, but also the development of polyethylene glycol-supported TsDPEN systems. Recently, we reported the synthesis of ion-tagged chiral ligands for asymmetric synthesis in water or ionic liquids, including the use for highly selective and efficient asymmetric transfer hydrogenation of aliphatic or aromatic ketones and imines in aqueous medium. …”
Section: Introductionmentioning
confidence: 99%
“…64 Novel derivatives of the C2-symmetric diamine used in arene/Ru(II) ATH catalysts continue to be developed, including a series of recently reported, pyridiniumcontaining examples which facilitate ATH in aqueous solution. 65 A further application of catalyst 18a in ATH was studied on dibenzo [b,f ][1,4]oxazepines substrates by Bhanage and More. 66 Preliminary studies revealed the catalyst system to be dependent on the pH of the reaction, in cases where the pH was greater than 5 the conversion decreased drastically and it was found that at pH 4 the conversion reached 99% and afforded the reduced product in 93% ee.…”
Section: Ruthenium-catalysed Imine Athmentioning
confidence: 99%
“…In 2017, Tan’s team reported the effective catalysis of asymmetric oxidation of sulfur in the aqueous phase by immobilizing imidazole ionic liquids on the surface of hydrophilic graphene sheets . Promotion of asymmetric reactions in water can be achieved by combining hydrophobic solid materials with hydrophilic ionic liquids. , Loaded ionic liquids in heterogeneous chiral catalyst can not only change the medium transfer in the reaction but also provide more catalytic active sites and improve the catalytic efficiency by functionalization of carriers. , However, at present, there are few reports on this aspect . Chiral catalysts that are suitable for aqueous systems and exhibit high catalytic activity, easy separation, and reusability have remained heretofore very limited in their development and application. …”
Section: Introductionmentioning
confidence: 99%
“…Chiral alcohols are important intermediates for the synthesis of various chiral drugs, perfumes, and pesticides, for which the asymmetric transfer hydrogenation of ketone compounds comprises a noteworthy preparation route. , Combinations of chiral ligand and transition metal are widely applied to this asymmetric transfer hydrogenation reaction. Asymmetric catalytic reduction of ketones in water has also attracted widespread attention. , Cationic chiral water-soluble ligands can promote asymmetric hydrogenation of aromatic ketones in water, while the hydrogenation reduction reaction of alkyl ketones remains undeveloped due to significant challenges . Chiral surfactant-type catalyst containing cation and long-chain alkanes was synthesized to achieve a micelle structure that can promote the highly reactive and selective hydrogen transfer reaction of alkyl ketones in water .…”
Section: Introductionmentioning
confidence: 99%